Pengembangan E-LKPD berbasis Project Based Learning (PjBL) pada Materi Laporan Keuangan - Anita; Neta Dian Lestari; Nova Pratiwi (Lembaga Anotero Scientific, 2024)
This research is a research that aims to develop E-LKPD based on Project Based Learning (PjBL) on financial report material at SMK Negeri 8 Palembang which can be tested valid, practical and learning outcomes. The method in this study is Research and Development (R&D) which uses the ADDIE model using data collection techniques in the form of interviews, questionnaires and tests. Based on the results of the study, it shows that E-LKPD based on Project Based Learning (PjBL) is declared valid according to the combined results of four validators with an average of 85.23% in the very valid category. In addition, its practicality has been proven from one-to-one tests with an average of 85.42% in the very practical category. As well as small group trials with an average of 85.25% in the very practical category. Furthermore, learning outcomes show an increase of 32.54% from the difference between pre-test and post-test. So that E-LKPD based on Project Based Learning (PjBL) is very suitable for use as a learning material.